Equine chorionic gonadotropin pretreatment 15 days before fixed-time artificial insemination improves the reproductive performance of replacement gilts - Q. Zhao (Elsevier, 2021)
Fixed-time artificial insemination (FTAI) technology uses exogenous reproductive hormones to regulate the sexual cycle and ovulation of sows without oestrus identification, which improves the sow breeding utilisation rate, reduces the number of non-productive days, and elevates the efficiency of pig farm management. In this study, we aimed to optimise FTAI procedures. Healthy 190-day-old and about 90 kg Large White × Landrace crossing breed replacement gilts (n = 166) which were of unknown reproductive status were randomly selected and divided into three groups: a control group (n = 62), an eCG-15D group in which the gilts were pretreated with equine chorionic gonadotropin (eCG) injection 15 days before starting FTAI (n = 50), and an eCG-20D group pretreated with eCG injection 20 days before starting FTAI (n = 54). All three groups were then subjected to the same conventional FTAI procedure. Pigs were orally administered Altrenogest (ALT, 20 mg per pig per day) for 18 days and then 42 h after ALT feeding was stopped, they were injected with 1 000 IU eCG followed by 100 μg GnRH 80 h later. The gilts were inseminated for the first time 24 h after gonadotropin-releasing hormone (GnRH) injection and then again 16 h later. After 42 h of ALT feeding, gilts in the eCG-15D group displayed a higher follicular diameter until artificial insemination (AI) than those from the other groups (P < 0.05). In addition, the ovulation times were the most synchronised in the eCG-15D group, with 100% of the gilts ovulating before the second AI on day 25 of FTAI. Furthermore, the gilts in the eCG-15D group achieved the highest pregnancy rate (92%), farrowing rate (90%), total pigs born (11.59), and pigs born alive (11.18). Together, the findings of this study demonstrate that reproductive performance can be optimised by pretreating gilts with eCG 15 days before conventional FTAI.